2020
DOI: 10.3390/ijerph17093108
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Comorbidity in Hepatocellular Carcinoma: A Network Perspective

Abstract: Hepatocellular carcinoma (HCC) is a common and fatal cancer. People with HCC report higher odds of comorbidity compared with people without HCC. To explore the association between HCC and medical comorbidity, we used routinely collected clinical data and applied a network perspective. In the network perspective, we used correlation analysis and community detection tests that described direct relationships among comorbidities. We collected 14,891 patients with HCC living in Jilin Province, China, between 2016 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…The results showed a strong association between liver cancer, cirrhosis and chronic viral hepatitis. The most common causes for liver cancer are chronic viral hepatitis B and C infection [39], and cirrhosis is a strong risk factor for liver cancer [40]. Liver cancer is frequently accompanied by one or more components of metabolic diseases, because metabolism is the most important function of the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed a strong association between liver cancer, cirrhosis and chronic viral hepatitis. The most common causes for liver cancer are chronic viral hepatitis B and C infection [39], and cirrhosis is a strong risk factor for liver cancer [40]. Liver cancer is frequently accompanied by one or more components of metabolic diseases, because metabolism is the most important function of the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Due to partly overlapping risk factors, the prevalence of cardiovascular disease (CVD) in the general population, and the incidence in similar age groups, arterial hypertension, coronary heart disease, cerebrovascular disease, and thromboembolic events are frequent comorbidities in patients with HCC. 58 Patients with uncontrolled CVD or recent acute events, such as myocardial infarction, pulmonary embolism or stroke, are excluded from clinical trials assessing systemic treatments for HCC (Table 1). A large cross-sectional Chinese study (n = 22,500) showed that of 2,574 patients with advanced HCC, 25.1% had concomitant hypertension, 4.7% had coronary heart disease, 3% atrial fibrillation, and 2% heart failure.…”
Section: Patients With Significant Cardiovascular Diseasementioning
confidence: 99%
“…According to the global HCC BRIDGE (“Bridge to Better Outcomes in HCC”) study [ 4 ], among the 18,031 HCC patients in 14 countries, the mean age of onset in Japan, Europe, and North America was 69, 65, and 62 years, respectively, and in China and South Korea, 52 and 59 years, respectively. In a Chinese study [ 5 ] that included 14,891 cases of HCC from 2016 to 2018, the proportion of patients ≤ 39, 40–49, 50–59, 60–69, and ≥ 70 years old was 2.89, 14.59, 29.47, 35.26, and 17.79%, respectively; the proportion of male and female patients was 76.01% and 23.99%, respectively.…”
Section: Epidemiologymentioning
confidence: 99%